Childhood family violence and officer responses to officer-involved domestic violence: Effects of cumulative and resolved trauma - Prost, Stephanie Grace (International journal of police science & management, 2020)
Law enforcement officers who witness or experience abuse in their family of origin are at higher risk of post-traumatic stress disorder (PTSD) and alcohol abuse. These trauma effects may, in turn, affect officers’ responses to domestic violence victims who call on them for help. The purpose of this study was to examine how these childhood traumas, PTSD, and alcohol abuse affect officers’ supportive responses to victims and perpetrators of officer-involved domestic violence (OIDV). We hypothesized that officers who witnessed or experienced family of origin violence would have higher levels of PTSD and abusive drinking than those without trauma. Furthermore, we hypothesized that officers with resolved trauma (i.e., no current PTSD or abusive drinking) would be more likely to support victims of OIDV than officers with unresolved trauma. Survey respondents were law enforcement officers (n = 1661) in police and sheriff’s departments throughout the United States. Results partially supported the hypotheses regarding the separate and cumulative effects of witnessing family violence and experiencing child abuse. In addition, officers who endured these childhood traumas, but resolved these concerns reported a significantly greater average likelihood of helping an OIDV victim than those with unresolved trauma. Implications include the promotion of employee assistance programs and professional counselors to support officers with unresolved trauma, which may lead to improved responses to OIDV.